Effect of living arrangements on health status of the elderly in Malaysia - Abdullah, Norehan; Samsudin, Shamzaeffa (Prof.(Dr) RK Sharma, 2019)
Malaysia needs to prepare now to address the ageing society problem, which is expected to account for 15% of the population by 2035. The increasing number of the elderly in the total population means there is an increasing incidence of ill health and chronic diseases. The World Health Organization in 1977 has described elderly people living alone as an ‘at risk’ group. Living alone in later life is often seen as an undesirable state and as a potential health risk. It is therefore crucial to understand the relationship between living arrangement and health status for the old age. Using a sample of 1, 414elderly from the northern Peninsular of Malaysia, this paper aims to examine the effect of living arrangement of Malaysian elderly's on the health status. The study found that living alone nor living with spouse, children or others is not significant in affecting the health status of elderly, but the physical aspect of living in own-home does matter to the probability of perceiving good health.